Parental Strategies in Managing L1 Interference in Early Second Language Acquisition: An Intrinsic Case Study - Jaelani, Alan; Rafli, Zainal; Murtadho, Fathiaty (JOLLT Journal of Languages and Language Teaching, 2025)
Drawing upon naturalistic data since the intake of English at the age of two, this longitudinal intrinsic case study examines the developmental trajectories of bilingual subject realization in an Early Second Language Acquisition (ESLA). Early bilingual exposure is widely recognized for its cognitive and linguistic benefits, yet challenges such as first language (L1) interference remain underexplored. This study focuses on a single child’s unique language learning journey which offers an in-depth exploration of how specific parental strategies, including exclusive use of English at home, curated media exposure, and interactive language use, contribute to the child reaching a CEFR B2 level by age seven. Despite the supportive language environment, this study identifies consistent patterns of L1 interference in areas such as syntax, word order, and morphology. Using qualitative analyses of spontaneous speech data, this study identifies recurring error patterns and their implications for bilingual language development. The findings emphasize the dual role of parental influence in fostering second language (L2) proficiency while also revealing structural challenges that necessitate personalized corrective strategies. This research offers practical insights for parents and educators in emphasizing the need for targeted interventions to mitigate L1 interference and optimize bilingual acquisition outcomes.